Investigation of Freeze-Thaw Resistance of Stabilized Saline Soil - Yongxiang Zhou; Qingfeng Guan; Peiyu Yan (Advances in Civil Engineering)
In this paper, three freezing-thawing tests are designed to study the freeze-thaw resistance of stabilized sulfate type saline soil. The results show that different destructive modes and erosion extents are caused by different freeze-thaw conditions. The destructive effect from salt tends to be limited if there is no external water intrusion. When sufficient water is provided, ice expansion, dissolution recrystallization of salts, and ettringite growth during the thawing phase may take place. Soil water potential is used for analysis and explanation of the driving force and water migration in the stabilized soil. Pressure potential caused by the air sealed in the stabilized soil specimen leads to early water concentration in the outer parts of the specimen, and the surface layer is first eroded under the freeze-thaw cycles. A high percentage of soil stabilizer can improve the freeze-thaw resistance of stabilized soil, but a sufficiently long curing period plays a more important role. This study provides useful insights for improving the freeze-thaw resistance of solidified saline soil in road engineering.